Handbook of Obesity Prevention A Resource for Health Professionals - Kumanyika, Shiriki; Brownson, Ross.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Comprehensive in scope and meticulously researched, Handbook of Obesity Prevention analyzes the intricate causes of this public health crisis, and sets out concrete, multilevel strategies for meeting it head-on. This innovative handbook starts by clearly defining obesity in clinical, epidemiologic, and financial terms. From there, expert contributors provide insights on current issues, methods, and controversies in the field, focusing on new opportunities for prevention, successful interventions and initiatives, and guidelines for planning and implementing programs and evaluating results. This systematic approach to large-scale social and policy change gives all parties involved—from individual practitioners to multinational corporations—the tools to set and attain realistic goals based on solid evidence and best practice in public health. A sample of topics covered: The individual: risk factors and prevention across the lifespan, specific populations (pregnant women, ethnic and regional groups). Levers for change in schools and workplaces. Prevention in health care systems: roles and resources. Community settings: role of the physical environment. "De-marketing" obesity: food industries and the media. Grassroots action: consumers and communities. The global obesity epidemic: rapid developments, potential solutions. From obesity prevention to health promotion: the future of the field. Its level of detail and wide range of topics make the Handbook of Obesity Prevention a bedrock sourcebook, overview, reference, or teaching text. Read by topic or cover to cover, here is accurate, up-to-date information for professionals and students in all areas of public health.
Why Obesity Prevention? -- What is Obesity? Definitions Matter -- Descriptive Epidemiology of Obesity in the United States -- Costs of Obesity -- Obesity Prevention Concepts and Frameworks -- Consumer Perspectives and Consumer Action -- The Role of Government in Preventing Obesity -- Planning and the Built Environment:Implications for Obesity Prevention -- The Food Industry Role in Obesity Prevention -- Media, Marketing and Advertising and Obesity -- Global Context of Obesity -- Organizational Change for Obesity Prevention—Perspectives, Possibilities and Potential Pitfalls -- Community-Based Approaches to Obesity Prevention: The Role of Environmental and Policy Change -- Health Care System Approaches to Obesity Prevention and Control -- Workplace Approaches to Obesity Prevention -- Obesity Prevention in School and Group Child Care Settings -- Individual Behavior Change -- Obesity Risk Factors and Prevention in Early Life: Pre-Gestation through Infancy -- Obesity Prevention During Preschool and Elementary School-Age Years -- Obesity Prevention During Preadolescence and Adolescence -- Obesity Prevention During Adulthood -- Obesity Prevention: Charting a Course to a Healthier Future.
Keywords: Psychiatry; Medicine; Health promotion; Public health; Psychiatry; Medicine/Public Health, general; Health Promotion and Disease Prevention; Public Health